Knowledge, attitude and perceived barriers towards conducting research among students in a medical college, India - Vairamani, Chibi R.; Akoijam, Brogen S. (International Journal Of Community Medicine And Public Health, 2018)
Background: Health research is a low priority area in the developing world, mostly due to inadequate research budgets and financially not rewarding venture. Medical students have a limited understanding of research and what it entails. Training on research theory to application, is an important but neglected part of medical education curriculum in the country, which needs to be paid more attention. The objective of the study was to assess the knowledge, attitude and perceived barriers towards conducting research among medical students in a remote medical college of India. Methods: This cross sectional study was done in the easternmost medical college of India during November-December 2015. A self-administered questionnaire was used to collect data from postgraduates and interns. Data were summarized using descriptive statistics. Chi-square test was used for comparing proportions. A p-value of <0.05 was considered significant. Results: Out of the total 493 eligible participants, 440 responded to the questionnaire. More than 3/5th of the respondents had inadequate level of knowledge of conducting research. Inadequate training (87%), lack of funding (76%), lack of motivation (67%) and no mentorship program (66%), were the major reasons cited by the respondents for not participating in research projects. Ever conducted research was associated with better knowledge of research. Majority of the participants wanted to know more about research. Conclusions: The study revealed inadequate knowledge but a positive attitude towards research. Sufficient training in research methods, skills and institution of mentorship program can boost participation in research.